Isolation and identification of Candida species from urogenital tract infections of women in Baghdad city: Alwan M.J. and Aziz M.M. - Alwan, Mohammed J. (The Iraqi Journal of Veterinary Medicine, 2012)
In order to determine Candida Species isolates that associated with urogenital infection in women,174 vaginal swabs and 66 urine samples were collected from pregnant and non-pregnant women suffering from urogenital tract infection whom visted teaching Al-way hospital during the peroid from January to October 2011. The results showed that 32 out of 174 vaginal swabs were Candida Spp positive (18.3%), high percentage was reported in June and July (25%) for each one and no fungal isolates were recorded in March .The results also explained that high percentage of fungal isolates was recorded in pregnant women (68.7%) as comparing with non-pregnant women (31.2%) .Thirty –two fungal isolates were recorded which included : C.albicans(43.7%); C.tropicals(21.8%), C.prarapsilosis(12.5%) ;C.glabrata (9.3%);C. guilliermondii(6.2%); C. capitatum and C. krusei (3.1%) for each one . Also the study revealed that 9 out 66,(13.6%) of the urine samples were Candida spp positive which included : C.albicans was form high percentage (7.5%) followed by C.tropicals(4.5%) and C.glabrala (1.5%), these results indicated that albicans and non-albicans Candida may be associated with urogenital infection in women.